2022
DOI: 10.1007/s00426-022-01676-w
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualizing mind wandering from a switching perspective

Abstract: Mind wandering is a universal phenomenon in which our attention shifts away from the task at hand toward task-unrelated thoughts. Despite it inherently involving a shift in mental set, little is known about the role of cognitive flexibility in mind wandering. In this article we consider the potential of cognitive flexibility as a mechanism for mediating and/or regulating the occurrence of mind wandering. Our review begins with a brief introduction to the prominent theories of mind wandering—the executive failu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 184 publications
1
7
0
Order By: Relevance
“…The similar RTs for the trials leading up to mind-wandering versus on-task reports during task-switching performance (see Table 2, unshaded rows) provided further evidence to support our previous argument that when one mind wanders during performance of a taskswitching paradigm, they continue to engage in a "task-switching mind frame" (i.e., instead of switching between task-related mental sets, they switch between task-related and taskunrelated mental sets), and thereby can maintain task-switching performance (Wong et al, 2022a). Furthermore, partly in line with our second prediction, we found a main effect of thought-probe response at the Pz electrode, with higher mean P300 amplitude for selfreported mind-wandering switch trials than self-reported on-task switch trials.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The similar RTs for the trials leading up to mind-wandering versus on-task reports during task-switching performance (see Table 2, unshaded rows) provided further evidence to support our previous argument that when one mind wanders during performance of a taskswitching paradigm, they continue to engage in a "task-switching mind frame" (i.e., instead of switching between task-related mental sets, they switch between task-related and taskunrelated mental sets), and thereby can maintain task-switching performance (Wong et al, 2022a). Furthermore, partly in line with our second prediction, we found a main effect of thought-probe response at the Pz electrode, with higher mean P300 amplitude for selfreported mind-wandering switch trials than self-reported on-task switch trials.…”
Section: Discussionsupporting
confidence: 76%
“…We believe that exploring the similarities/differences in the electrophysiological signature associated with mind-wandering versus on-task switch trials may provide further insight into whether mind wandering promotes a mental set suited to the requirements of task-switching paradigms (Wong et al, 2022b). For example, if similar RTs are observed for mindwandering switch trials and on-task switch trials (behavioral results) but mind-wandering switch trials are found to be associated with higher P300 amplitude (ERP results), this would indicate that: despite self-reported mind-wandering switch trials requiring more revision of the representations and/or more executive control resources than self-reported on-task switch trials, the competition between task-unrelated and task-related mental sets is less intense, which could be attributable to participants being in a "task-switching mind frame" (Wong et al, 2022a).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations